Analysis of solar cooling systems for fruit and vegetable storage warehouses - Bobur T. Shodiyev; Akram M. Mirzabayev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: this study investigates the potential of solar thermal cooling technologies as sustainable alternatives to traditional electricity-driven cooling systems, driven by the increasing global demand for cooling, projected to triple by 2050. Solar thermal systems, including absorption, adsorption, and ejector cooling systems, leverage renewable energy sources to reduce greenhouse gas emissions and energy consumption significantly. Aim: quantitatively, solar thermal collectors achieve efficiencies ranging from 50-80%, depending on the type, with absorption systems demonstrating a coefficient of performance (COP) of 0.6-0.8, while ejector systems exhibit a thermal COP of 0.3-0.5 and adsorption systems range from 0.2-0.6. In contrast, photovoltaic systems are limited to an efficiency of 16-18% when converting solar energy to cooling. Furthermore, solar thermal cooling systems can cover 30-50% of annual cooling demands in high solar irradiance zones, substantially decreasing reliance on conventional energy sources. Methods: qualitatively, these systems offer benefits such as reduced noise, simplified maintenance, and adaptability to various thermal sources, making them economically viable in both residential and industrial applications. Despite the higher initial capital costs, advancements in materials and design are anticipated to enhance their operational efficiency. Results: overall, solar thermal cooling technologies represent a scalable solution for sustainable cooling, aligning with global energy efficiency goals and mitigating dependency on fossil fuel-derived electricity. Future research is crucial for improving thermal performance and cost-effectiveness, facilitating broader adoption and competitiveness with conventional cooling technologies.